IMPLEMENTASI MODEL PENGEMBANGAN BISNIS BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) - Susilowati, Etty; Istikomah, Kartini; Laksmiwati, Mia; Rolanda, Ivo (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose-The purpose of the research is to design the BPRS business model will become a benchmark for the preparation of the Syariah banking operational business framework.Design/methodology/approach-The data collection method is the Questionnaire or Questionnaire method. The study population was BPRS in DKI Jakarta, West Java, and Banten Provinces, the study sample was BPRS Harta Insan Karimah, BPRS Al Salaam, and BPRS HIK Insan Cita. Data is processed using the Structural Equation Model (SEM) analysis method with Smart PLS application.Findings- Product, system and procedure variables, human resources and technology did not have a significant effect while infrastructure and location variables had a significant effect on customer decisions in choosing an SRB service.Implications- Information technology in BPRS must be applied to all business processes in order to face competition and continue to develop in the industrial era 4.0. Keywords: Business Model, BPRS, Information Technology